Reconstruction of Deep Learning-Based Practices in Islamic Education: An Analytical Study of the Hadith “Naddarallahu Imra'an” and Michael Fullan’s Framework - Shintia Faradina; Muhammad Sholihin; Iqbal Kholidi (An-Nasyi'in: Jurnal Ilmu Pendidikan, 2025)
This investigation explores how the prophetic tradition (hadith) of Prophet Muhammad,